Pengaruh Integritas Siswa terhadap AcademicFraud: Dimensi Fraud Pentagon Theory (Studi Kasus Pada Siswa di Podok Pesantren Nurul Hikmah Kabupaten Lombok Barat) - Muliani, Muliani; Febriana, Widia; Ayu, Baiq Dinda Puspita (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study was conducted to see the effect of student integrity on the tendency of academic fraud to occur using the fraud pentagon perspective. The existence of a fraud pentagon and student integrity are important factors that can be expected to reduce academic fraud. For this reason, this researcher aims to examine the effect of the pentagon fraud on academic fraud and the effect of student integrity on academic fraud. This research was conducted at the Nurul Hikmah Islamic Boarding School, West Lombok Regency, using primary data by distributing questionnaires to collect data and determine respondents based on non-probability sampling and purposive sampling. In accordance with the criteria that have been set, the questionnaire was given to students at the SMP and SMK levels at the Nurul Hikmah Islamic Boarding School. The proposed hypothesis was tested using multiple regression analysis. The results show that the pentagon fraud has a positive effect on academic fraud, and student integrity has a negative effect on academic fraud.Keywords: student integrity, fraud pentagon, academic fraud and Islamic boarding school